Photocatalytic Activity of Titania/Polydicyclopentadiene PolyHIPE Composites - Yuce, Elif; Mert, Emine Hilal; Krajnc, Peter; Parin, Fatma Nur; San, Nevim; Kaya, Dila; Yildirim, Huseyin (WILEY-V C H VERLAG GMBH, 2017)
Macroporous polymer composites with photocatalytic activity are prepared by the polymerization of surface modified TiO2 nanoparticle stabilized high internal phase emulsions. Poly(ethylene glycol-b-propylene glycol-b-ethylene glycol) triblock copolymer is used to synthesize surface modified TiO2 anatase via a sol-gel method. Macroporous composites are obtained by the ring opening metathesis polymerization of dicyclopentadiene within the particle-stabilized high internal phase emulsion templates. Photocatalytic activity of the resulting macroporous polymer composites is described by the kinetic data of the heterogeneous photocatalytic degradation reaction of 4-nitrophenol.
Keywords: macroporous polymers; nanocomposites; photocatalysis; polyHIPE; titania; SOL-GEL METHOD; INTERNAL PHASE EMULSIONS; POROUS TIO2; ACTIVATED CARBON; DEGRADATION; WATER; SURFACTANT; POLYMERS; FOAMS; POLYMERIZATION; Materials Science; Polymer Science